Comparative Study of the Characteristics of Nano Silica-, Silica Fume- and Fly Ash-Incorporated Cement Mortars - Biricik, Hasan; SARIER, NİHAL (Univ Fed Sao Carlos, Dept Engenharia Materials, Laboratoria De Materiais Vitreos, Caixa Postal 676, Sao Carlos, 13565-905Sp, Brazil, 2014)
The structural characteristics of cement mortars, impregnated with nano silica (NS), silica fume (SF) and fly ash (FA), were comparatively studied using Fourier transform infrared spectrometer (FTIR), thermogravimeter-differential thermogravimeter (TG-DTG) and scanning electron microscope (SEM). The mechanical strengths of the specimens were determined at early (7th day) and standard (28th day) curing ages. The compressive strengths and flexural strengths developed in the mortar specimens containing NS particles were found considerably higher than those of the corresponding specimens of SF and FA over and above the control at both ages. FTIR, TG-DTG and SEM analyses results were consistent with the remarkable increase in the mechanical strength of the mortars with NS. These increases in the strengths of the mortars with NS are attributable to the nano sized particles and extensive surface area of NS. The nano sized particles, as nucleating agents, promoted the hydration of C3S and C2S and the formation of C-S-H phase. Plenty of active sites on the surface of NS particles induced their pozzolanic reactivity and the extent of bond formation between NS particles and free CH.
Keywords: nano silica; silica fume; fly ash; mortar; FTIR; TG-DTG; Portland-Cement; Mechanical-Properties; Colloidal Nanosilica; Nano-Sio2 Particles; Concrete; Microstructure; Strength; Pastes; Nanoparticles; Systems